2009
DOI: 10.1159/000215386
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of <i>Helicobacter pylori</i> Eradication on Body Mass Index and Dyspeptic Symptoms

Abstract: Background and Aim: The relationship between Helicobacter pylori infection and body mass index (BMI) and dyspeptic symptoms is controversial. We investigated the changes in BMI and dyspeptic symptoms after H. pylori eradication among stages of atrophic gastritis classified according to the serum pepsinogen (PG) I/II ratio. Methods: One hundred and sixty-three H. pylori-positive patients underwent eradication therapy for H. pylori. Serum PG I and II concentrations were measured before treatment, and the PG I/II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Of the 34 H. pylori studies, 12 examined the effect of eradicating H. pylori on body weight or BMI status. With the exception of two studies (6,7), all other studies consistently found an increase in weight gain or increase in biomarkers associated to weight gain after H. pylori eradication (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Weight gain was observed across BMI ranges and was higher than control populations where H. pylori was not eradicated.…”
Section: Infections Linked With Changed Body Mass Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 34 H. pylori studies, 12 examined the effect of eradicating H. pylori on body weight or BMI status. With the exception of two studies (6,7), all other studies consistently found an increase in weight gain or increase in biomarkers associated to weight gain after H. pylori eradication (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Weight gain was observed across BMI ranges and was higher than control populations where H. pylori was not eradicated.…”
Section: Infections Linked With Changed Body Mass Indexmentioning
confidence: 99%
“…While the numbers of studies in these additional categories are small, some results are trending in specific directions. For example, the prevalence of periodontal disease, respiratory Helicobacter pylori (6)(7)(8)(9)(10)(11)(12)(13)(18)(19)(20)(21)(22)(23) Eradication is associated with weight gain Ad36 (37,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)195) Associated with obesity and fat mass gain Post-surgical infections Higher incidence of surgical site infections, post-operative infections, deep sternal wound infections and blood stream infections in obese patients. Longer hospital stays and more readmissions in obesity Class 2 and 3 obesity (BMI > 35 and 40) is associated with more severe post-surgical infection.…”
Section: Is the Outcome Of Infection Different In Obesity?mentioning
confidence: 99%
“…Additionally, similar long-term e ect of H. pylori eradication was observed among prepubertal children (Francois et al, 2011;Fujiwara et al, 2002;Osawa et al, 2006;Pacifico et al, 2008). However, Suto et al noticed that the e ect of H. pylori eradication on BMI is dependent on the serum pepsinogen I/II ratio (Suto et al, 2009). Interestingly, experiments conducted by Nwokolo et al, who for the first time examined the e ect of H. pylori eradication in H. pylori asymptomatic patients, showed a significant increase of the ghrelin level a er therapy.…”
Section: Impact Of H Pylori Infection and Anti-helico-mentioning
confidence: 71%
“…However, some conditions such as Helicobacter pylori infection or use of nonsteroidal anti-inflammatory drugs suppress GKN1 expression and it will be of interest to determine whether these impact metabolism or adiposity in ways consistent with those observed in GKN1 −/− mice 37,38 . Although controversial, H. pylori eradication is associated with increased BMI [39][40][41] but whether this is related to restoration of GKN1 expression is not known. Other factors might explain increased BMI following H. pylori eradication, such as resolution of dyspepsia or normalization of gastric ghrelin expression resulting increased appetite.…”
Section: Discussionmentioning
confidence: 99%